2021
DOI: 10.1002/agj2.20570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of latitude on maize kernel weight and grain yield across China

Abstract: Latitude influences maize kernel weight (KW) and grain yield by variation in climatic conditions such as temperature and solar radiation. In this study, the major aim is to examine the spatial variation in 1,000-KW and grain yield of the same maize hybrids and to further understand the differences in the response of 1,000-KW and maize grain yield to climatic factors under a wide range of latitude. For this purpose, we conducted field experiments at 17 different locations in the North maize region (NM) and Huan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…A number of studies have shown that the maize plantation distribution in the study area is highly correlated with temperature change [17,39,40], and agricultural production in this area is more sensitive to global climate annual variability [21,22,[41][42][43][44][45], as shown in the results of this study. For the middle-and high-latitude crop plantation belt, on one land, climate warming increases the heat resources in these areas and widens the area suitable for crop plantation, which tends to expand to high-dimensional and high-altitude areas.…”
Section: Discussionsupporting
confidence: 67%
“…A number of studies have shown that the maize plantation distribution in the study area is highly correlated with temperature change [17,39,40], and agricultural production in this area is more sensitive to global climate annual variability [21,22,[41][42][43][44][45], as shown in the results of this study. For the middle-and high-latitude crop plantation belt, on one land, climate warming increases the heat resources in these areas and widens the area suitable for crop plantation, which tends to expand to high-dimensional and high-altitude areas.…”
Section: Discussionsupporting
confidence: 67%
“…The average harvest age during the dry season (101.18 days) was higher than during the rainy season (98.97 days). The harvest age of maize was highly affected by air temperature [41,42]. Low air temperatures would cause a longer harvest age [43,44].…”
Section: Effects Of Genotype × Environment Interactions On Harvest Ag...mentioning
confidence: 99%